2002
DOI: 10.1177/07419325020230060401
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of the People

Abstract: Since 1986, the National Network for Educational Renewal (NNER) has attempted to persuade 41 institutions of higher education (IHEs) in partnership with schools to build collaborative networks among education faculty in colleges, schools, and departments of education (CSDEs) and to put into practice a new order of things leading to improvement in schooling and the renewal of teacher education. In an effort to describe the level of participation of special education in the commitment to the NNER agenda, we cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…That is, perceiving edTPA as a useful assessment for learning to educate SWLDs is not dependent on perceptions of the general preparation program but instead is related to the messages and perceived utility of edTPA more generally. This finding is in line with the results of prior research on the successful implementation of performance assessments, which illustrates that this reform depended on agreement from faculty on the assessment’s purpose such that it aligned with program goals as well as their quality of support of preparing candidates for the assessment (Ledwell & Oyler, 2016; Ratner & Kolman, 2016; Smith & Edelen-Smith, 2002).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…That is, perceiving edTPA as a useful assessment for learning to educate SWLDs is not dependent on perceptions of the general preparation program but instead is related to the messages and perceived utility of edTPA more generally. This finding is in line with the results of prior research on the successful implementation of performance assessments, which illustrates that this reform depended on agreement from faculty on the assessment’s purpose such that it aligned with program goals as well as their quality of support of preparing candidates for the assessment (Ledwell & Oyler, 2016; Ratner & Kolman, 2016; Smith & Edelen-Smith, 2002).…”
Section: Discussionsupporting
confidence: 86%
“…With rapid and radical changes in expectations for public schools in regard to educating students with disabilities, it is no surprise that many teacher education programs have lacked a coherent vision for how to best prepare teacher candidates for educating SWLDs. For example, Smith and Edelen-Smith (2002) surveyed 28 department chairs at universities with teacher education programs and found that there was an overall lack of agreement from faculty on the appropriate integration of expectations and competencies for teacher candidates in their programs. Based on these results, the authors speculated that these institutions would experience significant obstacles fostering collaboration between departments in schools of education to improve the training for candidates learning how to teach in inclusive classrooms.…”
Section: Preparation For Teaching Swldsmentioning
confidence: 99%